Participatory evaluation of municipal obesity prevention clubs in Tehran city: Strengths, challenges, and future direction - Edalati, Sareh; Omidvar, Nasrin; Takian, Amirhossein; Rasam, Farzaneh; Ghodsi, Delaram; Majdzadeh, Reza (Frontiers in Public Health, 2023)
Background and aim Community-based initiatives are important for obesity prevention. This study aimed to evaluate activities of municipal obesity prevention clubs (OBCs) in Tehran, Iran, using a participatory approach. Methods The evaluation team was made and the members identified the OBCs strengths, challenges and suggestions for change through holding a participatory workshop, observation, focus group discussions, reviewing relevant documents (n=97), and 35 interviews with involved stakeholders. MAXQDA software was used for data analysis Results Empowerment training programs for volunteers was identified as one of the strengths of OBCs. Despite obesity prevention efforts of OBCs in holding public exercise, healthy food festivals and training sessions, several challenges were identified that hinder participation in OBCs. These challenges included poor marketing strategies, poor training approaches in participatory planning, insufficient motivational support for volunteers, low perceived recognition of volunteers by community, volunteers’ low food and nutrition literacy, poor educational services in the communities, and limited funding for health promotion activities. Conclusions Weaknesses in all stages of community participation, including informing, consulting, collaboration and empowerment in OBCs was detected. Facilitating a more enabling environment is recommended for informing and involving citizens, expanding neighborhood social capital, and involving health volunteers, academia, and all potential governmental sectors to collaborate for obesity prevention.